2022
DOI: 10.3390/nano12050768
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport Studies of Encapsulated Topological Insulator Bi2Se3 Nanoribbons

Abstract: The majority of proposed exotic applications employing 3D topological insulators require high-quality materials with reduced dimensions. Catalyst-free, PVD-grown Bi2Se3 nanoribbons are particularly promising for these applications due to the extraordinarily high mobility of their surface Dirac states, and low bulk carrier densities. However, these materials are prone to the formation of surface accumulation layers; therefore, the implementation of surface encapsulation layers and the choice of appropriate diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the last decade, Bismuth is a pioneer in topologically insulating nanomaterials (TIs), from strong or weak of 3D TI, topological metals TIs, semimetals TIs to magnetic TIs, while retaining the usual layered structural patterns [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Bi 2 Se 3 TI thin films and nanoribbons with 1D Mohr stripe films on the surface, having a strongly enhanced surface density of states TI 1D cloudy superstructure due to weak coupling between the layers, became ideal candidates for van der Waals structures 3D TI [15]; 3D TI of Bi 2 Se 3 nanoribbons due to their very high mobility of surface Dirac states and low bulk carrier density [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, Bismuth is a pioneer in topologically insulating nanomaterials (TIs), from strong or weak of 3D TI, topological metals TIs, semimetals TIs to magnetic TIs, while retaining the usual layered structural patterns [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Bi 2 Se 3 TI thin films and nanoribbons with 1D Mohr stripe films on the surface, having a strongly enhanced surface density of states TI 1D cloudy superstructure due to weak coupling between the layers, became ideal candidates for van der Waals structures 3D TI [15]; 3D TI of Bi 2 Se 3 nanoribbons due to their very high mobility of surface Dirac states and low bulk carrier density [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that ZT of thermoelectric materials typically stays around 1.0 [14][15][16][17][18][19][20]. The conversion efficiency of Bi 2 Te 3 is low, but low power applications are gradually gaining the attention of researchers [21][22][23][24][25][26][27][28]. Currently, a wide range of demands have been developed for low-power generation and cooling technologies, the applications of which primarily operate in room-or low-temperature environments, such as micro-motor power systems, IoT wireless sensing modules, and wearable intelligent samples [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a hydrothermal method has been proven to be a feasible method to change the morphology and size of the synthesized Bi 2 Te 3 nanostructures with low equipment and operating requirements, low cost, and low synthesis temperatures. Considerable effort has shown the synthesis of Bi 2 Te 3 , Bi 2 Se 3 , Sb 2 Te 3 , BiTe, and PbTe nanomaterials by using a solvothermal method [13,[19][20][21][22][23][24][25][26][34][35][36][61][62][63][64]. Some studies reported the effect of the morphology of the products, but the synthesis method was not "green", and some reported that the synthetic method was "green," but the morphological changes were not reported.…”
Section: Introductionmentioning
confidence: 99%